Center for ecology and sports development and the Red Cross on the coast of Gazivode Lake - inspired by nature and tradition - Tomasella, Paolo (Arhitektura i urbanizam, 2020)
The design and development of the Center for Ecology and Sports Development and the Red Cross of Kosovo and Metohija introduced a new solution to the problem of protection and management of part of the Gazivodе Lake shore, an area of ​​the national importance. The uniqueness of the complex is reflected in its multifunctionality, which basically consists of water protection and monitoring, education, humanitarian activities, sports and recreational facilities and underwater research, which are located within the exceptional ambience of Gazivode Lake. The architecture of the buildings, colored by the national tradition and the specific ecological purpose, contribute to the impression of the careful fitting of the artefacts into the environment, made up of the unity of nature and the layered cultural and historical heritage. Through the final realization, the newly built complex justified the basic conceptual starting points of the authors according to their statement, which are finding the character of the place, discovering the potential of a wider context and harmony.